High dispersion and cubic-quintic-septic-nonic nonlinearity effects on optical solitons in the complex Ginzburg-Landau equation of eighth-order with multiplicative white noise in the Itô sense - Zayed, Elsayed M. E.; Arnous, Ahmed H.; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa; Shah, Nehad Ali; Chung, Jae Dong (ELSEVIER, 2024)
In this article, we present the complex Ginzburg-Landau equation involving eighth-order dispersion and multiplicative white noise effect in the context of Ito sense for the first time. In order to investigate and analyze the proposed model, two efficient and convenient techniques have been employed in this study. The results revealed the presence of various solitons, including bright, dark, and singular solitons. Additionally, the existence of straddled solitons was reported as well. These findings contribute to the current understanding of soliton dynamics and provide valuable insights for further research in this field. To better understand our findings, we have included several graphs that effectively illustrate the effect of the white noise. The white noise effect refers to a specific pattern of random fluctuations that can be observed in various systems and phenomena. It is characterized by a uniform distribution of frequencies across the entire spectrum, resulting in a constant and uncorrelated signal.
Keywords: Wiener process; Stochastic; Perturbations complex Ginzburg-Landau; equation; Enhanced Kudryashov technique; Noise intensity; Materials Science; Physics